The National States Rights Party a history - Newton, Michael 1951- (McFarland & Company, Inc., Publishers, 2017)
"Founded in 1958 by members of America's first postwar domestic Nazi-inspired movement, the National States Rights Party developed both as a political protest movement and as a vehicle of violent resistance to the black civil rights movement of the 1950s and 1960s. Its acts of terrorism made international headlines and claimed multiple lives"...